Leveraging User-Generated Content As A Marketing Communication Strategy - Iing Saefudin (Sean Institute, 2024)
This study aims to analyze the use of User-Generated Content (UGC) as an effective marketing communication strategy in increasing consumer engagement and building brand image. In the digital era, UGC, which is user-generated content such as reviews, photos, videos, and testimonials, has become an influential marketing tool because it provides authenticity and trust to consumers. This study uses a qualitative descriptive approach with data collection through literature studies. The results of this study indicate that the use of User-Generated Content (UGC) in marketing communication strategies can have a positive impact on consumer trust and engagement. UGC, which is considered more authentic because it comes from real consumer experiences, has succeeded in increasing user interaction with brands and expanding marketing reach through content sharing. Additionally, while UGC has many benefits, the study also identified several challenges, such as moderation issues, negative content, and the importance of maintaining brand consistency. With the right strategy, companies can overcome these challenges and maximize UGC’s potential to build stronger emotional connections with consumers and improve overall brand image .